KONSEP GURU DAN PENDIDIKAN AKHLAK MENURUT IMAM AL-GHAZALI - Nukman, Nukman; Munandar, Didih Syakir; Darisman, Dede (Jurnal Penelitian Pendidikan Islam, 2015)
This research was conducted to analyze the concept of teachers and moral education according to Al-Ghazali contained in Ihya Ulumuddin. The results of the study can be summarized as follows: 1) The concept of teachers and moral education according to Imam Al-Ghazali in the translation of the Book of Ihya Ulumuddin that teachers or educators are people who try to guide, improve, perfect and purify the heart so that it becomes close to the Khaliq. He also gave great attention to the task and position of an educator. This is reflected in his writing: "The best is what he says is knowledge"; 2) The concept of moral education according to Imam Al-Ghazali is a process of eliminating the reprehensible traits that exist in themselves and inculcating praiseworthy qualities, which aim to produce human beings and draw closer to Allah so that humans can obtain happiness in the world and the hereafter. Moral education proposed by Al-Ghazali emphasizes more on the element of the soul which has a central position in human beings so that in the moral education method he chooses to use the method of tazkiyah al nafs, mujahadah, and riyadhoh.